Oncologic and reproductive outcomes after fertility-sparing management with oral progestin for women with complex endometrial hyperplasia and endometrial cancer. Issue 1 (January 2016) - Chen, Ming; Jin, Ying; Li, Yan; Bi, Yalan; Shan, Ying; Pan, Lingya
Abstract: Objective: To investigate the oncologic and reproductive outcomes after progestin treatment of complex endometrial hyperplasia (CEH) and grade 1 endometrial carcinoma (EC). Methods: In a retrospective study, data were obtained for patients aged 20–42 years with CEH or grade 1 EC at presumed stage IA (without myometrial invasion) who wished to preserve fertility and were treated at the Peking Union Medical College Hospital, China, between January 1, 2000, and December 31, 2011. Patients had received oral medroxyprogesterone acetate (250–500 mg/day) or megestrol acetate (160–480 mg/day) for at least 6 months. Response to progestin treatment was assessed histologically. Results: Among 53 included patients, 39 (74%) achieved complete response after a median period of 6 (3–24) months. Complete response was less frequent among obese than nonobese patients (4/12 [33%] vs 35/41 [85%]; P = 0.001). Disease recurrence was recorded in 10 (26%) patients with complete response; the 5-year recurrence-free survival rate was 71%. Among the 33 patients who retained a desire to conceive, 17 (52%) became pregnant. Conclusion: Fertility-sparing management with oral progestin is effective. Obesity is associated with a lower probability of long-term success.